Methyl (2E)-2-({2-[(2E)-2-benzylidene-3-methoxy-3-oxopropyl]-1,3-dioxoindan-2-yl}methyl)-3-phenylprop-2-enoate - Lakshmanan, D. (International Union of Crystallography, 2012)
In the title compound, C31H26O6, the five-membered ring of the indane unit adopts a slight envelope conformation with the flap atom displaced by 1.38 (14) Å. The molecular conformation is stabilized by an intramolecular C—H⋯O hydrogen bond, which generates an S(9) ring motif. In the crystal, pairs of C—H⋯O hydrogen bonds link centrosymmetrically related molecules into dimers, generating R 2 2(22) ring motifs. The crystal packing is further stabilized by C—H⋯π interactions.